Tracing Lost Editions of Parisian Printers in the Sixteenth Century: The Case of Jean Bonfons and his Widow Catherine Sergent. (16th September 2020) - Adam, Renaud
Abstract: This article examines the lost production of a sixteenth-century Parisian family of printers, the Bonfons. This family, who specialized mainly in medieval vernacular romances, was chosen because the survival rate of their publications is relatively low and the number of lost editions high. Such study goes beyond the strict framework of bibliometry to raise two questions: do bibliographies really reflect what was published at that time? And, as a corollary, do survival rates distort our perception of early-modern book production? Previous research on the Bonfons's production is complemented by an outstanding source that has never been investigated in this context: the archives of the Commission of the Index of Prohibited Books of Antwerp (printed in 1570). In this light, the number of books printed for or by Jean Bonfons and his widow should be revised to almost 200 editions, with an average loss rate of around 40 per cent.